Social sustainability studies in the 21st century: A bibliometric mapping analysis using VOSviewer Software - Francoise Contreras; Ghulam Abid (Pakistan Journal of Commerce and Social Sciences (PJCSS), 2022)
The purpose of this study is to provide a bibliometric analysis of social sustainability literature in the business and management field, produced from 2001 to April 2021. The information was retrieved from the WoS database and the VOSviewer Software was used for data analyses. The analyses allowed us to identify the most influential authors, the most cited articles, the most highly cited journals, and the countries that have made the most relevant contribution to building this field of knowledge. Likewise, we conducted a references co-citation to identify the author and topics that constitute the foundations of this topic in the business area. Likewise, the co-occurrence network analysis for popular keywords was conducted, obtaining 4 clusters that indicate the main streams of the study of social sustainability research. Besides, a content analysis was conducted in the five resultant clusters of bibliographic coupling identifying the main themes studied in social sustainability in the business and management field. Finally, a co-citation analysis was conducted. This bibliometric mapping research concludes that social sustainability has acquired an increasing academic interest by scholars, according to the number of publications retrieved in WoS. Furthermore, result is corroborating by the co-word analysis, which shows that social sustainability in business and management has been mainly centred on corporate social responsibility and sustainable development. The detailed results of this bibliometric study and its practical implications are discussed.
Keywords: 330; social sustainability; sustainable organizations; bibliometric studies; bibliometric mapping; big data